2004
DOI: 10.1128/jvi.78.14.7478-7489.2004
|View full text |Cite
|
Sign up to set email alerts
|

Gene Profiling of Cottontail Rabbit Papillomavirus-Induced Carcinomas Identifies Upregulated Genes Directly Involved in Stroma Invasion as Shown by Small Interfering RNA-Mediated Gene Silencing

Abstract: While high-risk human papillomaviruses (HPVs) have been identified as necessary risk factors for the development of cervical cancer (7), the role of HPV in skin cancer, which is the most common cancer in Caucasians, is still undefined (3, 23). A first link between papillomaviruses and skin cancer was obtained in 1935 from an animal model system, when Rous and Beard (40) described the development of squamous cell carcinomas (SCCs) in rabbits after experimental infection with cottontail rabbit papillomavirus (CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…1) between WT E2, mutant R37K, and mutant I73A, suggesting that changes in the cellular gene expression that maybe caused by WT E2 and the mutant R37K but not by the I73A mutant could play a role in the tumorigenesis caused by CRPV. Indeed, in earlier gene expression profiling studies with CRPV-infected New Zealand White rabbits, we showed that during tumor progression several cellular genes involved in tumor invasion and cell motility become up-regulated (14). To identify the molecular basis for the different tumorigenic activity of the E2 transactivation domain mutants, we looked for differences between skin tumors induced by CRPV WT genome or by mutant genomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) between WT E2, mutant R37K, and mutant I73A, suggesting that changes in the cellular gene expression that maybe caused by WT E2 and the mutant R37K but not by the I73A mutant could play a role in the tumorigenesis caused by CRPV. Indeed, in earlier gene expression profiling studies with CRPV-infected New Zealand White rabbits, we showed that during tumor progression several cellular genes involved in tumor invasion and cell motility become up-regulated (14). To identify the molecular basis for the different tumorigenic activity of the E2 transactivation domain mutants, we looked for differences between skin tumors induced by CRPV WT genome or by mutant genomes.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the mutant E2 proteins had lost their ability to transactivate artificial promoters with multiple E2-binding sites, but all maintained their DNA-binding and replication capacities (13). On the cellular level, we identified tumor-promoting candidate genes by comparing the gene expression profiles of benign versus malignant rabbit skin tumors, which revealed proteins involved in cell motility, tumor invasion, and metastasis that are up-regulated in the process of CRVP-induced cancer progression (14). The transition from benign to invasive tumors is most likely not only dependent on the neoplastic cells themselves but also strongly affected by the interaction of neoplastic cells with their extracellular matrix (15).…”
Section: Introductionmentioning
confidence: 99%
“…Calpain activity appears to play a central role in the movement of immune cells (Lokuta et al, 2003;Stewart et al, 1998), thereby participating in the development of inflammation in normal and pathological conditions such as chronic inflammatory disease (Cuzzocrea et al, 2000;. Furthermore, calpain 2 expression is upregulated in some cancers and has recently been associated with disease progression in patients with breast cancer (Rios-Doria et al, 2003;Wang et al, 2005;Carragher et al, 2004;Huber et al, 2004). The coordinate regulation of adhesion structures by calpains and Src tyrosine kinases places calpains in a crucial role at the interface of kinase and protease cascades that regulate migration of tumor cells and their invasive properties (Carragher et al, 2001;Carragher and Frame, 2002;Carragher et al, 2002;Mamoune et al, 2003).…”
Section: Calpains In Human Diseasementioning
confidence: 99%
“…41 Moreover, 14-3-3zeta shows a constant upregulation of the transcripts in a cottontail rabbit papillomavirus squamous carcinoma model employing New Zealand 14-3-3zeta in cancer X Yang et al White rabbits. 42 A web-based meta-analysis (Oncomine) reveals 14-3-3zeta overexpression in various types of carcinomas, 41 suggesting its oncogene property. Based on these evidences, we suggest that 14-3-3zeta is a candidate proto-oncogene and deserves further investigation into its role in carcinogenesis.…”
Section: Oncogenementioning
confidence: 99%